Economic consequences of and resilience to a disruption of petroleum trade: The role of seaports in U.S. energy security. (April 2018) - Rose, Adam; Wei, Dan; Paul, Donald
Abstract: Despite increased domestic production, the U.S. is still importing more than one-third of its crude oil needs, the vast majority via ocean tankers. At the same time, there are increasing concerns about the vulnerability of ports and terminals to man-made and natural disasters. This paper advances a methodology for estimating the total economic consequences of and resilience to a disruption of crude oil and refined petroleum product trade at a major seaport. The methodology is able to estimate not only the direct impacts of such disruptions but also the supply-chain effects. It also estimates the effects of muting the impacts by various resilience tactics such as ship re-routing, drawing inventories from storage, accessing the Strategic Petroleum Reserve, geographic shifting of petroleum refining, and production rescheduling. We apply the methodology to a 90-day disruption of petroleum trade at the twin seaports of Beaumont and Port Arthur, Texas. The results indicate that port region and national economic activity could decline by billions of dollars, but that resilience can reduce these consequences significantly. We also conclude that factors associated with the recent surge in the extraction of shale and tight oil resources has significantly enhanced the potential effectiveness of some resilience tactics. Highlights: Seaports are increasingly vulnerable to disruptions from man-made and natural threats. Petroleum import and export disruptions are transmitted up and down supply chains. Resilience tactics can significantly dampen regional and national economic impacts. Not all seaports may be critical to regional and national energy security. The recent shale-oil boom has contributed to the resilience of the US energy system.